1968
DOI: 10.1126/science.162.3853.562
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Mobility: Determination by Soil Thin-Layer Chromatography

Abstract: Pesticide movement was evaluated by the comparison of R(F) values on thin layers of soils. Results from the new technique correlated well with existing information on pesticide movement, facilitating the grouping of pesticides into classes on the basis of mobility. Thin-layer chromatography may have broad applicability in soils research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(73 citation statements)
references
References 16 publications
3
70
0
Order By: Relevance
“…K oc values of three MC variants were calculated from their K d values in the three soils, the average values for MC-RR, LR and Dha 7 LR were 224, 46.3 and 84.8 respectively (Table 3). According to McCall and Helling's classifications (Table 4) (McCall et al, 1980;Helling and Turner, 1968), MC -LR belongs to a very high mobility class, Dha 7 LR belongs to a high mobility class and RR belongs to a medium mobility class. The results in Table 3 show the GUS values range from 1.48 to 2.06 for RR, 1.82 to 2.88 for LR and 1.76 to 2.09 for Dha 7 LR.…”
Section: Leach Behavior Of Mcs In Chinese Agriculture Soilsmentioning
confidence: 99%
“…K oc values of three MC variants were calculated from their K d values in the three soils, the average values for MC-RR, LR and Dha 7 LR were 224, 46.3 and 84.8 respectively (Table 3). According to McCall and Helling's classifications (Table 4) (McCall et al, 1980;Helling and Turner, 1968), MC -LR belongs to a very high mobility class, Dha 7 LR belongs to a high mobility class and RR belongs to a medium mobility class. The results in Table 3 show the GUS values range from 1.48 to 2.06 for RR, 1.82 to 2.88 for LR and 1.76 to 2.09 for Dha 7 LR.…”
Section: Leach Behavior Of Mcs In Chinese Agriculture Soilsmentioning
confidence: 99%
“…On the other hand, thin-layer chromatography is a simple and quick to measure herbicide mobility between soils (Helling and Turner, 1968), though the results are less precise than column measurements and, therefore, the method is not well accepted nowadays (Wauchope et al, 2002).…”
Section: Retentionmentioning
confidence: 99%
“…absorbing capacity, granulometric composition, cultivation measures). On the basis of studies concerning the translocation of herbicide active ingredients Helling & Turner (1968) determined the relative mobility index of herbicides (R f ), dividing them into five classes. In another study showed that chlorsulfuron (ALS group) was capable of penetrating to a depth of 50 cm 63 days after application, despite the fact that a bigger part of its residue was detected in a layer up to 25 cm deep.…”
Section: The Behavior Of Herbicides In the Soil Environmentmentioning
confidence: 99%